Preface to Special Issue “Mathematical Modeling and Data Science for Biology and Medicine” - Takashi Suzuki (Mathematics)
This Special Issue, titled “Mathematical Modeling and Data Science for Biology and Medicine”, aims to highlight the development and growing application of mathematical models and data science in medicine, as well as their role in enhancing the understanding and clinical management of various diseases [...]